2020
DOI: 10.21203/rs.3.rs-36820/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential causes and consequences of rapid mitochondrial genome evolution in thermoacidophilic Galdieria (Rhodophyta)

Abstract: The Cyanidiophyceae is an early-diverged red algal class that thrives in extreme conditions around acidic hot springs. Although this lineage has been highlighted as a model for understanding the biology of extremophilic eukaryotes, little is known about the evolutionary history of their mitochondrial genomes. To fill this knowledge gap, we sequenced five mitogenomes from representative clades of Cyanidiophyceae and identified two major groups, here referred to as Galdieria-type (G-type) and Cyanidium-type (C-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
4
5
0
Order By: Relevance
“…Moreover, it showed a relatively strong preference for the C‐base and that result was consistent with the study conducted by Cho et al. (2020), who reported that there was a certain correlation of base skew with the geographical location and environmental pressure of the species. It was speculated that this difference was attributed to the directional mutation of the mitochondrial DNA of A. chevalieri and A. cristatum , as the dominant bacteria of dark tea fermentation, under the long‐term influence of a special environment.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, it showed a relatively strong preference for the C‐base and that result was consistent with the study conducted by Cho et al. (2020), who reported that there was a certain correlation of base skew with the geographical location and environmental pressure of the species. It was speculated that this difference was attributed to the directional mutation of the mitochondrial DNA of A. chevalieri and A. cristatum , as the dominant bacteria of dark tea fermentation, under the long‐term influence of a special environment.…”
Section: Resultssupporting
confidence: 92%
“…Mitochondrial genomes features, such as genome size, number of CDS, synteny and high CG content are shared by all the isolates and consistent with those described in previous works [69,70]. As stated by Jain et al in 2015, the high GC skew could be a consequence of the heterotrophic life of G. sulphuraria , which requires an increase of the energy request from mitochondria when it finds itself living endolithically and in the dark [69].…”
Section: Discussionsupporting
confidence: 85%
“…For instance, the longest non-coding and most variable region in animal mitochondrial DNA is identified as Control Region (CR) and comprises a third strand of DNA, creating a D-loop [71]. In vertebrates this region has strand-specific bias and is involved in the asymmetric DNA replication mechanism [70,72].…”
Section: Discussionmentioning
confidence: 99%
“…High fluctuations in the availability of dissolved organic and inorganic carbon, light, temperature, etc. in these environments possibly selected for the maintenance of a metabolic flexibility (Gross, 1999; Gross et al., 2002; Ciniglia et al., 2004; Cho et al., 2020), which may have also allowed Cyanidiales to invade more moderate habitats (Yoon et al., 2006; Azúa‐Bustos et al., 2009; Castenholz & McDermott, 2010) and to disperse over long distances to geographically isolated extreme habitats (Rossoni et al., 2019a).…”
Section: Discussionmentioning
confidence: 99%